The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/app.46028
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced degradation properties of polypropylene integrated with iron and cobalt stearates and its synthetic application

Abstract: Synthetic plastic leads to environmental contamination, and a promising solution to this problem is to use prooxidants as fillers within them to speed up the photooxidation and thermooxidation processes. This makes plastics more susceptible to biodegradation. In this study, the degradation properties of the widely used polymer polypropylene (PP) were improved by integration with cobalt stearate (CoSt 2 ) and iron stearate (FeSt 3 ) as prooxidants with accelerating weathering degradation. The metal stearates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…After that point, a steep weight loss occurred until 400 °C. This loss was allied with the helix denaturation, skeletal degradation and destruction of peptide bridge chain linkage [39][40][41]. With this, there was decomposition of some volatile compounds such as HCN, H 2 S, CO 2 and H 2 O [42].…”
Section: Thermo Gravimetric Analysis (Tga)mentioning
confidence: 99%
“…After that point, a steep weight loss occurred until 400 °C. This loss was allied with the helix denaturation, skeletal degradation and destruction of peptide bridge chain linkage [39][40][41]. With this, there was decomposition of some volatile compounds such as HCN, H 2 S, CO 2 and H 2 O [42].…”
Section: Thermo Gravimetric Analysis (Tga)mentioning
confidence: 99%
“…The most common co-oxidants are complexes consisting of transition metals with stearic acid or other organic ligands [ 11 , 12 , 13 , 14 , 15 ]. In particular, stearic acid complexes of iron [ 16 , 17 , 18 , 19 ], cobalt [ 20 ], and manganese [ 21 ] can be added to the polyethylene matrix as co-oxidants to greatly accelerate its degradation rate. Studies have shown that iron stearate is a good photo-oxidation aid to initiate the photo-oxidative degradation of polyethylene, while manganese stearate mainly plays a role in the thermo-oxidative degradation of polyethylene [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefins such as polyethylene and polypropylene (PP) are polymer materials that are used in the textile industry for manufacturing plastic products for daily usage, such as sacks and yarns . PP, a thermoplastic polymeric material, is known for its outstanding cost‐to‐performance ratio, which has motivated researchers to improve its properties further, for example, by reinforcement with various inorganic fillers . The effectiveness of the general inorganic fillers in improving the mechanical and physical properties of polymers seriously depends on many factors, such as the ratio of filler, shape, size, surface characteristics, interfacial adhesion, and degree of filler dispersion .…”
Section: Introductionmentioning
confidence: 99%
“…1 PP, a thermoplastic polymeric material, is known for its outstanding costto-performance ratio, which has motivated researchers to improve its properties further, for example, by reinforcement with various inorganic fillers. [2][3][4][5][6][7] The effectiveness of the general inorganic fillers in improving the mechanical and physical properties of polymers seriously depends on many factors, such as the ratio of filler, shape, size, surface characteristics, interfacial adhesion, and degree of filler dispersion. [8][9][10][11] It has been reported that some inorganic fillers can increase the Young's modulus of polymer composites but cause a decrease in the tensile strength and toughness.…”
Section: Introductionmentioning
confidence: 99%